FDA approval summary: Crizotinib for pediatric and young adult patients with relapsed or refractory systemic anaplastic large cell lymphoma. Issue 8 (13th May 2022) - Merino, Margret; Kasamon, Yvette; Li, Hongshan; Ma, Lian; Leong, Ruby; Zhou, Jiaxi; Reaman, Gregory; Chambers, Wiley; Richardson, Nicholas; Theoret, Marc; Pazdur, Richard; Gormley, Nicole
Abstract: In January 2021, the U.S. Food and Drug Administration (FDA) approved crizotinib for pediatric patients 1 year and older and young adults with relapsed or refractory systemic anaplastic large cell lymphoma (sALCL). This is the first approval for pediatric sALCL. Approval was based on a single‐arm trial of crizotinib monotherapy that included 26 patients, aged 1–20 years, with previously treated sALCL. Efficacy was based on centrally assessed objective response rate (88%) and duration of response. Herein, we highlight unique aspects of the regulatory review, including extension of the indication to young adults, postmarketing safety, and dose optimization strategies.